2015
DOI: 10.1016/j.virol.2015.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Influenza D virus infection in Mississippi beef cattle

Abstract: A new member of the Orthomyxoviridae family, influenza D virus (IDV), was first reported in swine in the Midwest region of the United States. This study aims to extend our knowledge on the IDV epidemiology and to determine the impact of bovine production systems on virus spread. A total of 15 isolates were recovered from surveillance of bovine herds in Mississippi, and two genetic clades of viruses co-circulated in the same herd. Serologic assessment from neonatal beef cattle showed 94% seropositive, and presu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
179
4
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(200 citation statements)
references
References 12 publications
12
179
4
5
Order By: Relevance
“…Our virologic surveillance found that IDV was present in 23.6% of 55 calves affected with BRD but in only 2.4% of 82 healthy calves upon arrival at the same facility (4). Other studies have shown that the IDV positivity rates in cattle with BRD in the United States and France were 4.5% and 4.8%, respectively (3,6).…”
mentioning
confidence: 43%
See 2 more Smart Citations
“…Our virologic surveillance found that IDV was present in 23.6% of 55 calves affected with BRD but in only 2.4% of 82 healthy calves upon arrival at the same facility (4). Other studies have shown that the IDV positivity rates in cattle with BRD in the United States and France were 4.5% and 4.8%, respectively (3,6).…”
mentioning
confidence: 43%
“…Viral RNA was extracted using a GeneJet viral DNA/RNA purification kit according to the manufacturer's protocol (Thermo Scientific, Pittsburgh, PA). Gene-specific amplification primers were designed according to the D/swine/1334/Oklahoma/2011 sequence and a reverse transcription (RT) primer based upon the conserved noncoding regions, as described previously (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Siedem segmentów genomu nowego wirusa koduje 9 białek wirusowych: glikoproteinę (białko fuzyjne hemaglutynino-esterazę, HE), polimerazy (PB 1, 2 i 3), NP, białka matriks (M1 i CM2) oraz białka niestrukturalne (NS1 i NEP) (5).…”
Section: Struktura Genomuunclassified
“…Między innymi: nowy wirus posiada zdolność do replikacji in vitro w większej liczbie hodowli komórkowych niż ICV; różnił się powinowactwem do receptorów komórkowych, strukturą i miejscem wiązania białka fuzyjnego hemaglutynino-esterazy (HE) z receptorem; ekspresją białka matriks 1; sekwencją w regionach niekodujących; aktywnością neuraminidazy i O-acetyloesterazy; był zdolny do replikacji w temperaturze 37°C; nie dawał reakcji krzyżowych w testach serologicznych, a także nie ulegał reasortacji in vitro z ludzkimi szczepami ICV (2,5,6,22). Dowodzi to, że nowy wirus stanowi odrębny typ i z tego powodu jego szczep prototypowy przemianowano na D/swine/ Oklahoma/1334/2011 (D/OK).…”
unclassified